ANALISIS KEARIFAN LOKAL MASYARAKAT BENGKULU DALAM FESTIVAL TABOT BERDASARKAN RECEPTIO IN COMPLEXU THEORY - Megayanti, Sandra; Elcaputera, Arie (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2019)
Abstact : Local wisdom is part of the field of community life that reflects the cultural values. Every region in Indonesia has its own local wisdom, some of which is still preserved today. For the example, one of the local wisdoms in Bengkulu community, Tabot festival which is routinely held every year that it has religious values and local culture. But in its implementation, there are things that are debated, especially regarding the tendency for practices that are contrary with the values of Islam. Therefore, in this article will discuss about  the local wisdom of the Bengkulu people in the Tabot Festival and the concept of the Tabot Festival based on the Receptio In Complexu theory.Keywords: Local Wisdom; Tabot Festival; Receptio In Complexu Theory.